1988
DOI: 10.1111/j.1749-6632.1988.tb19555.x
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Estimator Model for Human Spatial Orientationa

Abstract: A model is presented to predict human dynamic spatial orientation in response to multisensory stimuli. Motion stimuli are first processed by dynamic models of the visual, vestibular, tactile, and proprioceptive sensors. Central nervous system function is modeled as a steady state Kalman filter that optimally blends information from the various sensors to form an estimate of spatial orientation. Where necessary, nonlinear elements preprocess inputs to the linear central estimator in order to reflect more accura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
103
0

Year Published

1994
1994
2021
2021

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 137 publications
(106 citation statements)
references
References 21 publications
3
103
0
Order By: Relevance
“…Other models utilized techniques borrowed from optimal estimation (Borah et al 1988;Ormsby and Young 1977). Ormsby's model included the influence of rotational cues on the orientation of gravity using a mechanism resembling an internal model of a physical relationship.…”
Section: Other Models Of Sensory Integrationmentioning
confidence: 99%
“…Other models utilized techniques borrowed from optimal estimation (Borah et al 1988;Ormsby and Young 1977). Ormsby's model included the influence of rotational cues on the orientation of gravity using a mechanism resembling an internal model of a physical relationship.…”
Section: Other Models Of Sensory Integrationmentioning
confidence: 99%
“…Research on modeling the vestibular signal processing aimed at developing theories of human spatial orientation perception, and was applied mainly to aerospace physiological studies. L. R. Young and his group proposed an optimal estimator model in [22]. He introduced the concept of internal model which comprised the dynamic model information about the sensory organs and head-neck system.…”
Section: Mathematical Models Of Vestibular Systemmentioning
confidence: 99%
“…Assumptions about sensor dynamics and noise statistics of the internal model were used to correct the estimated states which represented spatial orientation. Estimated states, called perceptions in [22], contained angular orientation of the head, its angular velocity, inertial translation and inertial velocity. Some nonlinear elements were added to the model in order to reproduce the delay of the onset of visually induced motion.…”
Section: Mathematical Models Of Vestibular Systemmentioning
confidence: 99%
“…Borah [11] suggested that the CNS functions were analogous to a Kalman optimal estimator when combining sensory cues, and introduced additional dynamics into vestibular responses due to these central processes.…”
Section: Observer Modelmentioning
confidence: 99%